On the Evolutionary Advantage of Coagulation Factor V Leiden (FVL) - Lindqvist, P.G. (Current Medicinal Chemistry, 2015)
Carriership of coagulation factor V Leiden (FVL) is by far the most common thrombophilia in Western populations. FVL is caused by a single point mutation in the gene coding for coagulation factor V (FV) causing a lifelong procoagulatory state with an increased risk of venous thromboembolism (VTE) which might be fatal. It is believed that the mutation occurred in one person 21,000 years ago and today 3% to 15% of the Western populations are carriers. A potentially dangerous mutation such as FVL ought to be rare and should have been reduced, if not eradicated, by selection during the course of human evolution. Thus, FVL must confer the carriers with an evolutionary advantage in order to be so prevalent. Lower risk of profuse bleeding and increased fecundity might give carriers an advantage. In this paper we give an updated short background and discuss possible evolutionary advantages and disadvantages.
Keywords: APC resistance